Communities of innovation how video game makers capture millions of dollars of innovation from user communities and you can too! - Edery, David 1976- (FTPress Delivers, 2010)
"This Element is an excerpt from Changing the game: how video games are transforming the future of business (ISBN: 9780132357814) by David Edery and Ethan Mollick. Unleash user-driven innovation beyond your wildest imagination, for a fraction of the cost of creating it yourself! Game companies have spent years learning to channel user passion into mutually beneficial work. These lessons are increasingly important to every industry because games aren't the only products that attract communities of user innovators"--Resource description page.